RespiDisk: a point-of-care platform for fully automated detection of respiratory tract infection pathogens in clinical samples. Issue 21 (2nd September 2020) - Rombach, Markus; Hin, Sebastian; Specht, Mara; Johannsen, Benita; Lüddecke, Jan; Paust, Nils; Zengerle, Roland; Roux, Louis; Sutcliffe, Thomas; Peham, Johannes R.; Herz, Christopher; Panning, Marcus; et al.
Abstract : The RespiDisk platform for automated detection of multiple viral and bacterial respiratory tract infection pathogens. Abstract : We present the RespiDisk enabling the fully automated and multiplex point-of-care (POC) detection of (currently) up to 19 respiratory tract infection (RTI) pathogens from a single sample based on reverse transcriptase polymerase chain reaction (RT-PCR). RespiDisk comprises a RTI-specific implementation of the centrifugal microfluidic LabDisk platform and combines new and existing advanced unit operations for liquid control, thereby automating all assay steps only by a spinning frequency and temperature protocol in combination with the use of a permanent magnet for in situ bead handing. The capabilities of the system were demonstrated with 36 tested quality samples mimicking clinical conditions (clinical and/or cultured material suspended in transport medium or synthetic bronchoalveolar lavage (BAL)) from past external quality assessment (EQA) panels covering 13 of the 19 integrated RTI detection assays. In total, 36 samples × 19 assays/sample resulting in 684 assays were performed with the RespiDisk, and its analytical performance was in full agreement with the routine clinical workflow serving as reference. A strong feature of the platform is its universality since its components allow the simultaneous detection of a broad panel of bacteria and viruses in a single run, thereby enabling the differentiation between antibiotic-treatable diseases. Furthermore, the full integration of all necessary biochemical components enables a reduction of the hands-on time from manual to automated sample-to-answer analysis to about 5 min. The study was performed on an air-heated LabDisk Player instrument with a time-to-result of 200 min.